ROLE OF WORK ATTITUDES AND ORGANIZATIONAL PERFORMANCE OF PUBLIC FINANCIAL INSTITUTIONS IN NEPALESE CONTEXT - Pandey , Dhruba Lal; Risal , Nischal; Basnet , Bhupindra Jung (Bangladesh Journal of Multidisciplinary Scientific Research, 2025)
The working attitude plays a pivotal role in the performance of employees in Nepalese public sector financial institutions because the environment in Nepal is hostile. Thus, the main issue of this article is to evaluate the relationship between work attitude and organizational performance. Work attitude is proxied by organizational commitment, organizational citizenship behaviour, and job involvement. This study aimed to explore the relationship between work attitudes and organizational performance. Two thousand two hundred fifty-one officer-level employees of Nepalese public financial institutions were the population. Among them, 310 is the sample size. Officer-level employees are the prominent ones who evaluate the attitude of the employees. Thus, the officer-level employees are considered as the population, and they are selected purposively. Therefore, the purposive sampling strategy is adopted to select the sample. CR, AVE, and MSE are used to test the reliability and validity. Path analysis tests the impact of organizational commitment, organizational citizenship behavior, and job involvement on organizational performance. The result unveiled that organizational commitment, organizational citizenship behavior, and job involvement have a positive and significant impact on organizational performance in Nepal’s public financial institutions. Modifications in organizational commitment, organizational citizenship behavior, and job involvement policies can leverage organizational performance in Nepalese public financial institutions. The study provides insights into the work attitude of public sector financial institutions and helps to frame policy. Similarly, it is a new issue in Nepal and provides insights and new literature in the academic sector of Nepal. JEL Classification Codes: C12, G20, M00.